PENGARUH PELATIHAN PENYUSUNAN LAPORAN KEUANGAN MASJID TERHADAP TINGKAT PEMAHAMAN REMAJA MASJID DALAM PENYUSUNAN LAPORAN KEUANGAN SESUAI SAK-ETAP - Ahmad Chuzairi (JURNAL CAFETARIA, 2023)
The mosque institution is a non-profit organization in the religious field, according to the Financial Accounting Standards for Entities Without Public Accountability (SAK-ETAP). The SAK is stipulated by the Indonesian Institute of Accountants (IAI) in ISAK-35 (Interpretation of Financial Accounting Standards) concerning the presentation of financial statements of non-profit oriented entities. For this reason, mosques must and have the right to produce financial reports that can be accounted for and reported to users of mosque financial reports. both internal and external entities. Accounting activities carried out include recording, classifying, summarizing, reporting, and analyzing organizational financial data. Therefore, Muslim institutions need accounting as a tool for financial management, planning and monitoring.